Complete genome characterization of Rocio virus (Flavivirus: Flaviviridae), a Brazilian flavivirus isolated from a fatal case of encephalitis during an epidemic in Sao Paulo state - Medeiros, Daniele B A; Nunes, Márcio R T; Vasconcelos, Pedro F C; Chang, Gwong-Jen J; Kuno, Goro (Journal of general virology, 2007)
The flaviviruses of major medical importance in South American countries are yellow fever, dengue, Saint Louis encephalitis, West Nile and Rocio viruses. Rocio virus (ROCV) has been responsible for epidemics of severe encephalitis in Brazil with a case-fatality rate of 10 % and development of sequelae in 20 % of the survivors. We have sequenced and characterized the entire genome of ROCV for the first time, by determining the general traits of the open reading frame and the characteristics of viral genes including the potential cleavage sites, conserved or unique motifs, cysteine residues and potential glycosylation sites. The conserved sequences in the 3'-non-coding region were identified, and the predicted secondary structures during cyclization between 5'- and 3'-non-coding regions were studied. Multiple protein and phylogenetic analyses based on antigenically important and phylogenetically informative genes confirmed a close relationship between ROCV and Ilheus virus (ILHV), together constituting a unique and distinct phylogenetic subgroup as well as the genetic relationship of ROCV with several members of the Japanese encephalitis group. Although ROCV is phylogenetically related to ILHV, our study shows that it is still a virus distinct from the latter virus. This is the first flavivirus uniquely indigenous to Brazil that has been sequenced completely and the genome characterized. The data should be useful for further studies at the molecular level, including construction of infectious clone, identification of gene function, improved disease surveillance based on molecular diagnostic tools and vaccine development.